Heterochrony and post-natal growth in mammals - an examination of growth plates in limbs - Geiger, M. (2014)
Mammals display a broad spectrum of limb specializations coupled with different locomotor strategies and habitat occupation. This anatomical diversity reflects different patterns of development and growth, including the timing of epiphyseal growth plate closure in the long bones of the skeleton. We investigated the sequence of union in 15 growth plates in the limbs of about 400 specimens, representing 58 mammalian species: 34 placentals, 23 marsupials and one monotreme. We found a common general pattern of growth plate closure sequence, but one that is universal neither between species nor in higher-order taxa. Locomotor habitat has no detectable correlation with the growth plate closure sequence, but observed patterns indicate that growth plate closure sequence is determined more strongly through phylogenetic factors. For example, the girdle elements (acetabulum and coracoid process) always ossify first in marsupials, whereas the distal humerus is fused before the girdle elements in some placentals. We also found that heterochronic shifts (changes in timing) in the growth plate closure sequence of marsupials occur with a higher rate than in placentals. This presents a contrast with the more limited variation in timing and morphospace occupation typical for marsupial development. Moreover, unlike placentals, marsupials maintain many epiphyses separated throughout life. However, as complete union of all epiphyseal growth plates is recorded in monotremes, the marsupial condition might represent the derived state.